Kesesuaian Lahan Tanaman Buah-buahan dan Perkebunan Berbasis Sistem Informasi Geografis Pada Lahan Kering di DAS Yeh Ho Kabupaten Tabanan - CHRIST ALVIN TIMOTHY SIREGAR; NI MADE TRIGUNASIH; I NYOMAN DIBIA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Land Suitability For Fruits Plants And Plantations Based On Geographic Information Systems On Dry Land In Yeh Ho Watershed, Tabanan Regency This research aims to discover the actual and potential of land suitability, limited factor, improvement effort, land use management, and the creation of land suitability maps and direction of use land for fruit plants and plantations. Plants that are evaluated include pomelo, durian, banana, passion fruit, vanilla, pepper, robusta coffee, arabika coffee, coconut and cocoa. The research was conducted in Yeh Ho Watershed Tabanan Regency from January 2020 to March 2020. The research method uses the land evaluation survey method. Land suitability assessment is carried out to the sub-class level, by matching the quality of the land with the growing requirements of the plants evaluated. The results showed that classes of actual land suitability for fruits plants and plantations are S1 (very suitable) until N (not suitable). The limited factors in the research area include: temperature, rainfall, dry month, humidity, texture, coarse material, soil depth, pH, salinity, slope, erosion hazard, surface rock, and the rock outcrops. Improvement of the land-suitability can be done with improvement effort except temperature, rainfall, humidity, coral material, surface rock, and rock outcrops because they are permanent barrier factor. Potential suitability class of land for some fruit plants and plantations evaluated are S1 (highly suitable) until S3 (marginal suitable), with limited factors among others temperature, rainfall, humidity, coarse material, surface rock, and rock outcrops factors. Land use recommendations on LCKIVKc and ACKIVTg for robusta coffee plants; ACKIVKc for pomelo plants; LCKIIKc for durian, banana, pomelo, coconut and pepper plants; LCKIIITg for pepper and vanilla plants; LCKIIIKc for pomelo and banana plants.